Nanomechanical resonators using functional nanowires - Ali, UE (2022)
Nanoelectromechanical systems (NEMS) have seen a surge of active interest in the 21st century. NEMS resonators have been initially employed for mass and force sensing as well as quantum mechanical measurements. With the recent developments in readout techniques at room temperature, NEMS have also proven promising in telecommunications and signal processing applications. Excitingly, NEMS devices operate at the sub-picowatt regime, which is many orders of magnitudes smaller than today’s digital signal processing blocks. Thus, nanomechanical signal processing is becoming an exciting area of research, with the aim of developing effective ways for transducing and tuning mechanical resonances. Currently, active tuning of NEMS is achieved by stress-tuning methods, which rely on the application of net forces to the resonator via electromagnetic fields. However, stress-tuning is volatile, which requires constant electrical stimuli (i.e. quiescent power) to maintain the tuned frequency. Stress-tuning also suffers from reliability issues and alters the quality (Q) factors of the resonators. To overcome these challenges, this thesis investigates a novel technique of tuning nanomechanical resonances by exploiting the Young’s modulus change in chalcogenide-based phase-change materials (PCMs). PCMs can be permanently yet reversibly switched between amorphous and crystalline states, which exhibit different elastic properties. This can be employed as a non-volatile tuning mechanism in NEMS resonators. Recent advances have also shown that nanowire configurations offer a more reliable and homogenous phase transition compared to thin-film PCMs. By using nanosecond-fast electrical pulses for phase-change and employing a piezoresistive readout scheme, the first instance of a non-volatile (power-free) tuning scheme in NEMS has been demonstrated within a range of ~30% using GeTe nanowires. The effect of phase-change on Q factors, phase noise, and piezoresistive gauge factors have also been studied. With non-changing Q factors over 16,000 and a decent phase noise performance, the GeTe nanowires have also been utilised in a frequency-hopping radio transmission. The promises of such a functional resonator are lower power consumption, faster tuning speeds, and better phase noise performance in commercial frequency synthesisers. To improve the signal-to-noise ratio for real-world applications, a novel transduction scheme for nanowires based on cavity optomechanics has further been demonstrated in this thesis, with transduction gain levels of 1.46 mV nm-1 for InP nanowires and 2.02 mV nm-1 for GeTe nanowires at an optical probe power < 75 µW. This thesis also investigates theoretically that these gain levels can be further improved by a factor ~200, extending the field of NEMS beyond academia for the first time, with imminent applications in signal processing and telecommunications. To assemble such a functional platform into a hand-held device, a novel pick-and-place technique has also been developed here, integrating single-crystal nanowires with on-chip devices with a placement precision below 1 µm.